Improvement of Electronic Governance and Mobile Governance in Multilingual Countries with Digital Etymology using Sanskrit Grammar - Arijit Das; Diganta Saha (IAES Indonesia Section, 2017)
With huge improvement of digital connectivity (Wifi,3G,4G) and digital devices access to internet has reached in the remotest corners now a days. Rural people can easily access web or apps from PDAs, laptops, smartphones etc. This is an opportunity of the Government to reach to the citizen in large number, get their feedback, associate them in policy decision with e governance without deploying huge man, material or resourses.But the Government of multilingual countries face a lot of problem in successful implementation of Government to Citizen (G2C) and Citizen to Government (C2G) governance as the rural people tend and prefer to interact in their native languages. Presenting equal experience over web or app to different language group of speakers is a real challenge. In this research we have sorted out the problems faced by Indo Aryan speaking netizens which is in general also applicable to any language family groups or subgroups.Then we have tried to give probable solutions using Etymology.Etymology is used to correlate the words using their ROOT forms.In 5th century BC Panini wrote Astadhyayi where he depicted sutras or rules- how a word is changed according to person,tense,gender,number etc.Later this book was followed in Western countries also to derive their grammar of comparatively new languages.We have trained our system for automatic root extraction from the surface level or morphed form of words using Panian Gramatical rules.We have tested our system over 10000 bengali Verbs and extracted the root form with 98% accuracy.We are now working to extend the program to successfully lemmatize any words of any language and correlate them by applying those rule sets in Artificial Neural Network.